2017
DOI: 10.1080/01913123.2017.1397075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol on high-fructose-induced testis injury in rats

Abstract: This study investigated whether a high-fructose (HFr) diet changes the morphology of seminiferous tubules (ST) in rats and resveratrol (RES) has a possible restoring effect in this sense. Fructose (30%; w/v) was administered to rats alone or together with RES (50 mg/L) in drinking water for 8 weeks. In the HFr group, destruction of the germinal epithelium led to the detection of immature germ cells in the lumen. HFr diet gave rise to a decrease in the ST diameters (p < 0.05), Johnsen's tubular biopsy score val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
5
14
0
1
Order By: Relevance
“…This was consistent with the basement membrane irregularities detected by electron microscope and with the widened interstitial spaces. Similar results were reported by Meydanli et al [52].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This was consistent with the basement membrane irregularities detected by electron microscope and with the widened interstitial spaces. Similar results were reported by Meydanli et al [52].…”
Section: Discussionsupporting
confidence: 92%
“…Dyslipidemia, a characteristic component of MetS was proved in this study by the significant increase in serum TG and LDL and decrease in HDL. This reproduced the results of previous studies [52,72]. Basaranoglu et al [17] declared that chronic fructose ingestion favors hepatic lipogenesis, by providing large amounts of hepatic triosephosphate as precursors for fatty acid synthesis, thus increasing lipid accumulation in the liver as well as its secretion and an increase in blood content.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Flavonoids are a group of compounds that are widely distributed in fruits and vegetables. Moreover, flavonoids, such as resveratrol, quercetin, and naringenin have been extensively investigated for the treatment of various types of testicular injury . In recent years, consuming vegetables and fruits containing luteolin has shown beneficial effects on the male reproductive system .…”
Section: Introductionmentioning
confidence: 99%
“…There was no difference in calorie content. Meydanli et al suggested that chronic high‐fructose intake in healthy individuals may suppress food intake in the long‐term. Fructose is thought to be associated with appetite hormones, including insulin, leptin, and ghrelin .…”
Section: Discussionmentioning
confidence: 99%